2022
DOI: 10.1093/mnras/stac033
|View full text |Cite
|
Sign up to set email alerts
|

Binary companions triggering fragmentation in self-gravitating discs

Abstract: Observations of systems hosting close in (<1 AU) giant planets and brown dwarfs (M ≳ 7 MJup) find an excess of binary star companions, indicating that stellar multiplicity may play an important role in their formation. There is now increasing evidence that some of these objects may have formed via fragmentation in gravitationally unstable discs. We present a suite of 3D smoothed particle hydrodynamics (SPH) simulations of binary star systems with circumprimary self-gravitating discs, which include a rea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…Fontanive et al (2019) found an inflated binary fraction of 80% with separations from 20-10,000 AU for stars hosting close in higher-mass planetary and brown dwarf companions (7-60 M Jup ). Cadman et al (2022) showed that the binary companions can trigger instability and fragmentation in gravitationally unstable disks, leading to formation of these giant planet and brown dwarf companions in outer regions of the disk, which somehow move to the close-in orbits currently observed. However other studies have concluded that the frequency of planets in binaries is not statistically different from that of single stars (e.g.…”
Section: Motivation: Substellar Companions In Wide Binariesmentioning
confidence: 98%
“…Fontanive et al (2019) found an inflated binary fraction of 80% with separations from 20-10,000 AU for stars hosting close in higher-mass planetary and brown dwarf companions (7-60 M Jup ). Cadman et al (2022) showed that the binary companions can trigger instability and fragmentation in gravitationally unstable disks, leading to formation of these giant planet and brown dwarf companions in outer regions of the disk, which somehow move to the close-in orbits currently observed. However other studies have concluded that the frequency of planets in binaries is not statistically different from that of single stars (e.g.…”
Section: Motivation: Substellar Companions In Wide Binariesmentioning
confidence: 98%
“…Despite the often disastrous influence close-in eccentric binary companions are understood to have on planet formation (exemplified by the dearth of planets found in binaries with separation 10 au seen in Fig. 1), the occurrence rate for hot Jupiter planet hosts having a stellar companion is twice as high as the binarity ratio of field stars with projected separations 20 -10000 au (Cadman et al 2022). A secondary star can modify the projected spin-orbit angle between primary star and planet (observed through measuring the Rossiter-McLaughlin effect), exciting secular evolution and interactions that cause a departure from coplanarity for all orbiting bodies (Martin & Lubow 2018;Franchini et al 2020;Moe & Kratter 2021;Best & Petrovich 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies show that a close stellar companion can impact planets through the truncation or misalignment of the protoplanetary disk (Artymowicz & Lubow 1994;Kraus et al 2012;Martin et al 2014), the formation and migration of gas giant planets (Dawson & Johnson 2018;Fontanive et al 2019), and the scattering of planets in unstable triple-star systems (Thebault & Haghighipour 2015). For example, recent simulations of protoplanetary disks around the primary star in wide binary systems (with separations a = 100-400 au) often result in the disk fragmentation needed to form giant planets (Cadman et al 2022). Modeling also predicts that the shape and size of the companion's orbit can play a significant role in planet formation, such that close, eccentric, or highly inclined companions could hinder planet formation (Holman & Wiegert 1999;Quintana et al 2002;Jang-Condell 2015;Cadman et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent simulations of protoplanetary disks around the primary star in wide binary systems (with separations a = 100-400 au) often result in the disk fragmentation needed to form giant planets (Cadman et al 2022). Modeling also predicts that the shape and size of the companion's orbit can play a significant role in planet formation, such that close, eccentric, or highly inclined companions could hinder planet formation (Holman & Wiegert 1999;Quintana et al 2002;Jang-Condell 2015;Cadman et al 2022).…”
Section: Introductionmentioning
confidence: 99%